2017
DOI: 10.1007/s00259-017-3809-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 18F-FDG PET/MRI and MRI for pre-therapeutic tumor staging of patients with primary cancer of the uterine cervix

Abstract: The present results demonstrate the successful application of integrated PET/MRI imaging for whole-body tumor staging of cervical cancer patients, enabling improved treatment planning when compared to MRI alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
59
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 33 publications
3
59
3
1
Order By: Relevance
“…Recently, the diagnostic potential of integrated PET/MRI has been reported in these situations. Use of 18 F-FDG PET/MRI correctly identi ed T stage (85%) in cervical cancer (22), suggesting that 18 F-FDG PET/MRI might be useful in the local evaluation of the ovarian cancer. In the assessment of T3b and T3c staging, ceCT has been widely used as the standard imaging modality for staging ovarian cancer.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Recently, the diagnostic potential of integrated PET/MRI has been reported in these situations. Use of 18 F-FDG PET/MRI correctly identi ed T stage (85%) in cervical cancer (22), suggesting that 18 F-FDG PET/MRI might be useful in the local evaluation of the ovarian cancer. In the assessment of T3b and T3c staging, ceCT has been widely used as the standard imaging modality for staging ovarian cancer.…”
Section: Discussionmentioning
confidence: 93%
“…In other cancers, including nasopharyngeal, breast, and colorectal cancers, 18 F-FDG PET/MRI has been reported as superior compared with 18 F-FDG PET/CT for detecting lymph nodes or distant metastasis (25). Moreover, 18 F-FDG PET/MRI has been reported as equivalent to MRI in cervical cancer (22) for the detection of lymph nodes or distant metastasis. Considering the results of the present study, which showed the superiority of 18 F-FDG PET/MRI to ceCT for M staging, 18 F-FDG PET/MRI might offer a useful alternative imaging modality to ceCT, or 18 F-FDG PET/CT in the assessment of N and M staging as well as in the T staging in ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive literature is found supporting the role of MRI in the pretreatment evaluation of patients with cervical cancer. MRI provided detailed findings being an advanced multi-planar multi-parametric modality that made staging and consequently management much easier procedure in a way that overweighs its high cost [7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…A specificity of 97% is reported when nodes are defined as metastatic in cases of short-axis larger than 1 cm [23]. In early cervical cancer, the positive predictive value and accuracy of MRI for detecting lymph node metastasis were reportedly 51-76% and 67-76% [7,24]. Lee et al proposed a treatment decision model based on pretreatment MRI findings [25].…”
Section: Discussionmentioning
confidence: 99%